2016
DOI: 10.15452/cejnm.2016.07.0012
|View full text |Cite
|
Sign up to set email alerts
|

Selected indicators of mental health in the elderly - the participants the University of the Third Age

Abstract: Aim: The aim of the research study is to identify the selected indicators of mental health, such as meaning of life, experience of well-being, hope, and feelings of loneliness and depression in the elderly participating in the University of the Third Age, in relation to their age and gender. Design: A quantitative descriptive study. Methods: The selection of respondents was deliberate. The sample consisted of 147 seniors with a mean age of 67.4 (± 4.9) years enrolled at the University of the Third Age at Jesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Although one finds no longitudinal research on the relationship between U3A membership, on the one hand, and improvement in physical and cognitive well-being, on the other, various cross-sectional studies outlined how U3As bring about direct benefits to their members' overall welfare (Maniecka-Bryła, Gajewska, Burzynska, & Byrla, 2013;Niedzielska et al, 2017;Zielinska-Wieczkowska, Ciemnoczołowski, Kedziora-Kornatowska, & Muszali, 2013). An association between participation in U3As and improved levels of self-assurance, self-satisfaction, selfesteem and sense of coherence, on the one hand, and a decline of depressive and anxiety symptoms, on the other, is a frequent result in both survey and ethnographic research (Tomagová, Farský, Bóriková, & Zanovitová, 2016). In the Polish context, researchers concluded that Participation in various forms of educational activity broadens one's horizons.…”
Section: The University Of the Third Agementioning
confidence: 99%
“…Although one finds no longitudinal research on the relationship between U3A membership, on the one hand, and improvement in physical and cognitive well-being, on the other, various cross-sectional studies outlined how U3As bring about direct benefits to their members' overall welfare (Maniecka-Bryła, Gajewska, Burzynska, & Byrla, 2013;Niedzielska et al, 2017;Zielinska-Wieczkowska, Ciemnoczołowski, Kedziora-Kornatowska, & Muszali, 2013). An association between participation in U3As and improved levels of self-assurance, self-satisfaction, selfesteem and sense of coherence, on the one hand, and a decline of depressive and anxiety symptoms, on the other, is a frequent result in both survey and ethnographic research (Tomagová, Farský, Bóriková, & Zanovitová, 2016). In the Polish context, researchers concluded that Participation in various forms of educational activity broadens one's horizons.…”
Section: The University Of the Third Agementioning
confidence: 99%
“…Dependendo dos cursos oferecidos aos idosos, os benefícios variam de saúde física, melhoras no bem-estar, na memória, na socialização, na autoestima, na capacidade funcional, no raciocínio, entre outros (Adamo et al, 2017;Zając-Gawlak et al, 2016;Tomágová et al, 2016;Zielinska-Wieczkowska, 2016;Działa, 2016).…”
Section: Universidades Da Terceira Idadeunclassified
“…It helps to mobilize intellectual and cognitive functions and to strengthen physical and mental health, and thus to life satisfaction. It creates an opportunity to acquire knowledge in various fields of science, to actively spend free time, increase the number and improve the quality of social relations, and also creates an opportunity for self-realization [20].…”
mentioning
confidence: 99%